Dynamic relationship between green bonds and major financial asset markets from the perspective of climate change - Gao, Lijun; Guo, Kun; Wei, Xianhua (Frontiers in Environmental Science, 2023)
In recent years, changes in the climate environment have caused a considerable impact on the economy and finance, especially after the signing of the Paris Agreement decided to prevent the further increase in the earth's temperature and smoothly transformed into a low-carbon society, various markets have been affected to varying degrees, and at the same time, green bonds as an emerging environmental protection tool have sprung up and become the focus of many investors and researchers. The emergence and rise of eco-friendly investment opportunities such as green bonds is bound to have an impact on other markets, but little research has been done on their dynamic correlation with the U.S. stock market, crude oil and gold markets, especially in our current period of COVID-19 tensions, it is necessary to explore the dynamics between markets and the risk aversion of green bonds to climate change. In this paper, we study the dynamic correlation between three green investment vehicles (S&P Green Bond, China Green Bond, and Climate Bond) and three major markets, and explore whether the linkage between each market will be affected by economic risks and climate change risks by adding climate risk proxy indicators and economic policy uncertainties. This is not only of guiding significance for investors who are eco-friendly to judge the effectiveness of asset allocation and hedging in investment decisions, but also has certain reference for policymakers and market participants who want to achieve green investment, which will help the market to maintain a stable and smooth transition to a low-carbon economy in the event of pressure.